Manajemen Sarana Pendukung Kurikulum dalam Peningkatan Mutu Pembelajaran di Pondok Pesantren Al-Kinanah Jambi - Umniyyah Hilwa (JMiE (Journal of Management in Education), 2023)
This study aims to describe the implementation of curriculum support facility management in improving the quality of learning for students at Al-Kinanah Islamic Boarding School in Jambi City. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the availability of learning facilities in the pesantren is still limited. This condition is reflected in the insufficient number of classrooms, the absence of a library building, and the lack of a laboratory. These limitations affect the conduciveness of the learning process. Nevertheless, the pesantren continues to strive to optimize the use of the available facilities. The main obstacles in managing the facilities include limitations in human resources, infrastructure, and budgetary support. These findings underscore the importance of more effective management of curriculum support facilities as one of the key factors in improving the quality of learning in pesantren environments.